Optimalisasi Kualitas Penyelenggaraan Pelayanan Publik pada Mal Pelayanan Publik Kota Cimahi: Analisis Servqual dan Soar - Yuskan, Muhamad Waris; Suwanda, Dadang; Thahir, Baharuddin (Universitas Batanghari Jambi, 2026)
This study aims to analyze public service quality through the ServQual framework, identify strategic factors through SOAR analysis, and formulate evidence-based optimization strategies. Using a qualitative descriptive method with a single case study design, data were collected through in-depth interviews, FGDs, observations, and document analysis involving 19 purposively selected informants. ServQual analysis reveals an overall gap of -1.09 (E=4.46; P=3.37), with Tangibles as the most critical dimension (-1.67) due to IT system downtime occurring 3–5 times monthly and queue formation phenomena beginning at 03:00–04:00 AM. SOAR analysis identifies strengths based on modern infrastructure and positive track records, opportunities from the national GovTech agenda, collective aspirations toward zero-hassle MPP, and eight measurable target results. The synthesis of both analyses produced 10 strategy clusters across three implementation phases. This research proposes ServQual-SOAR integration as an original analytical framework for MPP optimization that can be adopted nationally.